Aerosol-assisted synthesis of mesoporous aluminosilicate microspheres: the effect of the aluminum precursor. (25th April 2016) - Fiorilli, Sonia; Cauda, Valentina; Pontiroli, Lucia; Vitale-Brovarone, Chiara; Onida, Barbara
Abstract : Spray-dried mesoporous aluminosilicates, with spherical morphology, high surface area and accessible porosity, have been synthesized under mild acidic aqueous conditions by using different aluminum precursors. Abstract : The development of a cost-effective process for the production of mesostructured aluminosilicates, with high Al content and controlled morphology, is highly desired. In this work, mesoporous aluminosilicates, with spherical morphology, have been synthesized under mild acidic aqueous conditions by using an aerosol-assisted sol–gel process, a simple, versatile and potentially scalable method. Two aluminum sources, aluminum isopropoxide and aluminum chloride, have been used, keeping constant the other synthesis and process parameters. FE-SEM, coupled with EDX, TEM and N2 adsorption–desorption measurements have shown that sprayed powders consist of microspheres, homogeneous in size and characterized by high surface areas (up to 640 m 2 g −1 ) and narrow pore size distributions (centred at 2.5 nm). 27 Al-NMR spectra of as-synthesized samples have evidenced mostly tetrahedral Al, also for the sample with higher Al content (Si/Al = 5.7). The surface acidity of the sprayed samples has been investigated by FT-IR spectroscopy of adsorbed ammonia and CO, which has shown the presence of Brønsted sites (able to protonate ammonia) and of weak Lewis sites.